Jordan : Sixth Review Under the Stand-By Arrangement, Request for Waivers of Applicability of Performance Criteria, and Rephasing of Access. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Jordan's Sixth Review Under the Stand-By Arrangement, Request for Waivers of Applicability of Performance Criteria (PC), and Rephasing of Access. PC Program performance remains broadly on course. All end-March 2015 PCs are expected to be met. Structural performance saw improvement, including the pre-approval of a credit bureau and the establishment of a new public investment framework. There is an urgent need for broad-based policy actions in the labor market to put the unemployed into jobs, increase female labor force participation, and reform public-sector compensation and hiring practices. The IMF staff supports the completion of the sixth review and the related purchase.